2018
DOI: 10.1002/ajmg.b.32707
|View full text |Cite
|
Sign up to set email alerts
|

The array of clinical phenotypes of males with mutations in Methyl‐CpG binding protein 2

Abstract: Mutations in the X-linked gene MECP2 are associated with a severe neurodevelopmental disorder, Rett syndrome, primarily in girls. It had been suspected that mutations in MECP2 led to embryonic lethality in males, however such males have been reported. To enhance understanding of the phenotypic spectrum present in these individuals, we identified thirty males with MECP2 mutations in the RTT Natural History Study databases. A wide phenotypic spectrum was observed, ranging from severe neonatal encephalopathy to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 48 publications
0
48
1
2
Order By: Relevance
“…Eight male patients with MECP2 mutations were identified in this study, including two diagnosed with typical RTT, three with atypical RTT, and three with ID/DD. Previous studies have demonstrated various clinical phenotypes in males with MECP2 mutations, ranging from cognitive impairment to neonatal encephalopathy 32,33 . However, male patients in this study presented with a milder phenotype than most of the previously reported patients, and there were no such cases of encephalopathy reported in the current study.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…Eight male patients with MECP2 mutations were identified in this study, including two diagnosed with typical RTT, three with atypical RTT, and three with ID/DD. Previous studies have demonstrated various clinical phenotypes in males with MECP2 mutations, ranging from cognitive impairment to neonatal encephalopathy 32,33 . However, male patients in this study presented with a milder phenotype than most of the previously reported patients, and there were no such cases of encephalopathy reported in the current study.…”
Section: Discussioncontrasting
confidence: 74%
“…Male individuals with MECP2 mutations have actually been rarely reported worldwide, only about 100 males with MECP2 mutations have been reported 10,32 . Eight male patients with MECP2 mutations were identified in this study, including two diagnosed with typical RTT, three with atypical RTT, and three with ID/DD.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Mutations of methyl‐CpG binding protein 2 ( MECP2 ) on the X chromosome are identified in over 90% of patients with a typical RTT phenotype. MECP2 mutations were mainly identified in females with RTT and Rett‐like syndrome (RTT‐l), while males with MECP2 mutations mainly present with severe encephalopathy and fulfil the criteria of variant RTT as they develop (Neul et al, 2018; Soffer and Sidlow, 2016; Tokaji et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Rett syndrome is a rare disease, yet with 1 in 10-12,000 females [104][105][106][107], and fewer males [108][109][110][111], considered to have the disease, the number globally is not insubstantial. This thesis predominantly addresses issues related to the communications challenges, support needs and (hidden) potential of individuals with Rett syndrome.…”
Section: Relevancementioning
confidence: 99%